Criminological Analysis Of Physical Violence Committed By Teachers Towards Students - Anina Putri; Nursariani Simatupang; Faisal Faisal (Fakultas Hukum Dehasen, 2024)
Violence committed by teachers against students at school, both physical, psychological, and sexual violence, has a very bad impact on the psychological development of students. The researcher was used to find out the cause of physical violence committed by teachers on students. This research is normative juridical research which is descriptive in nature, using a statutory approach, the data in this research comes from secondary data. Data collection was carried out by means of library research, namely visiting the library directly or indirectly. The results of the study show that there are a number of efforts made by teachers to prevent their acts of violence against their students. One of these efforts is to maintain their professionalism as teachers, build good relationships, provide specialized training on how to teach students without using violence, enforce discipline for teachers and students who violate the rules, and provide additional sanction options in addition to direct sanctions.